In-band network telemetry system based on high-performance packet processing architecture VPP - Tian PAN; Xingchen LIN; Jiao ZHANG; Tao HUANG; Yunjie LIU (Tongxin xuebao)
An in-band network telemetry-based system was built based on VPP, a high-performance virtual network forwarding architecture/device, via reorganizing the data plane pipeline processing modules.Moreover, a network-wide telemetry mechanism was further developed via embedding source routing into the probe packet header for specifying the route of probe packets.Finally, a virtual network topology was built with performance evaluation conducted.The evaluation shows that the telemetry system can monitor the network in a high precision of every 0.13 ms, detecting link congestion in real time with minor performance overhead.Given virtual network devices have been widely deployed in data centers, the proposed scheme is expected to improve the reliability of multi-tenancy and network function virtualization in data centers via high-precision, network-wide virtual link telemetry coverage.